Analisis Faktor Penyebab Keterlambatan Penyediaan Berkas Rekam Medis RJ di RSUP dr. Soeradji Tirtonegoro Klaten - Diyana Wulandari; Andri Permana Wicaksono; Atma Deharja (Politeknik Negeri Jember, 2020)
The number of outpatient medical records at RSUP dr. Soeradji Tirtonegoro has the highest late provisionthat occurred in June 2019 by 44.66%. The purpose of this report was to analyze the factors causing lateprovision of outpatient medical record files at RSUP dr. Soeradji Tirtonegoro Klaten. This type of researchwas qualitative. Data collection techniques used in this report were interviews and observation. The resultsshowed that the factors causing late provision of outpatient medical record files was man factors, whichare the indiscipline of filing staff in retrieving medical record files and the poly / ward officers' indiscipline inreturning medical records in a timely manner. Material factors were damage to the medical record file onthe map, missfile, emergency patient form without a folder, and the form has not been assembled. Themachine factor were the sudden power failure and the lack of borrowing and returning medical records onSINERGIS. The method factor was the unavailability of regular outpatients in the registration room. Themoney factor is that there is no financial support to give awards to officers. Improvement efforts that can bedone are filing officers not waiting for some tracers to pile up when retrieving files, evaluating the processof returning outpatient or inpatient medical record files to the filing room, always sweeping againstdamaged or non-bound documents. IT added features or menus for borrowing and returning medicalrecord files to SINERGIS. The registration officer installs a regular outpatient registration flow in theregistration room.